MAPPING THE VILLAGE TOURISM STUDIES IN INDONESIA - Chawa, Anif Fatma; Putra, Moch Hisyam; Ambarsari, Zulia Antan (Jurnal Master Pariwisata (JUMPA); Volume 09, Nomor 02, Januari 2023, 2023)
This article aims to identify, map, and analyze the research related to village tourism in Indonesia conducted from 2011 to 2021. This bibliography-based study employed a charting-the-field method involving 233 studies published in national journals at least Sinta 3 accredited and international journals of four academic publishers including Elsevier, Springer, Wiley, and Emerald. This study presents a picture of topics, kinds, tourist destinations, research methods, number of citations, and journals rarely used but having received attention for further research on village tourism. Research findings show that the number of studies on village tourism increases every year, but there are several aspects not receiving attention or not being studied. The classification according to research sites shows that some studies are required to be conducted in the provinces outside Java and Bali islands. Research results further indicate that some research topics of local wisdom, the roles of the governments and stakeholders, and village tourism from the perspectives of gender and conflict and also assessment of village tourism management have not been studied. Similarly, the types of village tourism that have not received enough attention are education tourism, religious tourism, social tourism, and culinary tourism. The lack of these research aspects is observable by employing research methods which have not been used by many, including mix-methods and literature studies. Keywords: bibliography study; charting the field method; village tourism.